2014
DOI: 10.1557/opl.2014.118
|View full text |Cite
|
Sign up to set email alerts
|

Highly reliable passivation layer for a-InGaZnO thin-film transistors fabricated using polysilsesquioxane

Abstract: Polysilsesquioxane passivation layers were used to passivate bottom gate a-InGaZnO (a-IGZO) thin film transistors (TFT). The a-IGZO TFTs passivated with polysilsesquioxane showed highly stable behavior during positive bias stress, negative bias stress, and negative bias illumination stress. A voltage threshold shift of up to 0.1 V, less than -0.1 V and -2.3 V for positive bias stress, negative bias stress, and negative bias illumination stress, respectively. We also report the effect of reactive ion etching (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The enhanced device performance of a TFT with a thicker IGZO film can also be explained by the reduced DOS in the IGZO film. It is worth noting that device performances of passivated IGZO TFTs with O 3 -ALD Y 2 O 3 in the current study are comparable with previous reports, ,, together with the effective passivation of the defect states at the back-channel surface as compared to other passivation layers reported elsewhere. ,, Recently, Xie et al reported almost negligible V th shift after 2500 s of the NBIS test with 380 nm wavelength light with molybdenum-doped ZnO (MZO) as a UV shield layer and nitrogen-doped IGZO channel (IGZO:N). However, the degradation of device performance was observed with MZO-passivated IGZO:N TFTs as compared to unpassivated IGZO:N TFTs .…”
Section: Resultssupporting
confidence: 89%
“…The enhanced device performance of a TFT with a thicker IGZO film can also be explained by the reduced DOS in the IGZO film. It is worth noting that device performances of passivated IGZO TFTs with O 3 -ALD Y 2 O 3 in the current study are comparable with previous reports, ,, together with the effective passivation of the defect states at the back-channel surface as compared to other passivation layers reported elsewhere. ,, Recently, Xie et al reported almost negligible V th shift after 2500 s of the NBIS test with 380 nm wavelength light with molybdenum-doped ZnO (MZO) as a UV shield layer and nitrogen-doped IGZO channel (IGZO:N). However, the degradation of device performance was observed with MZO-passivated IGZO:N TFTs as compared to unpassivated IGZO:N TFTs .…”
Section: Resultssupporting
confidence: 89%
“…To contact the drain/source with electrical wiring, etching the passivation layer by RIE was performed, which affected the TFT's initial transfer characteristics [21]. Photosensitive material can form a contact hole through the passivation layer without RIE.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20][21] The use of organic passivation layers is one solution, given that organic passivation layers can be deposit at room temperature by a simple spin-coating or slot-coating processes, without inflicting plasma damage. [22][23][24] However, organic materials are not very good passivation layers because of their very high water vapor transmission rate (WVTR). In this work, we propose a fluorinated siloxane-based organic passivation layer.…”
mentioning
confidence: 99%